2019
DOI: 10.3390/ijerph16193779
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Treatment Enhanced the Skeletal Response to Exercise in Estrogen-Deficient Rats

Abstract: Estrogen deficiency frequently leads to a fall in estrogen receptor-α (ERα) numbers and then reduces the skeletal response to mechanical strain. It, however, is still unclear whether phytoestrogen administration will enhance the effects of exercise on the estrogen-deficient bone loss. This study aimed to determine the effect of Icariin treatment on the response of osteogenic formation to exercise in ovariectomized (OVX) rats. Thirty-two 3-month old female Sprague–Dawley rats were randomly allocated into four g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…It was reported that β-catenin, Akt, ERα, and Runx2 expression were significantly increased in OB in the treadmill-bound Epimedii intervention group, compared with exercise alone. Combination treatment significantly prevented OVX-induced bone loss and increased OB differentiation and mineralization ability, some of which may be regulated by the ERα/Akt/β-catenin pathway, but whether combination intervention affected OC differentiation remains unclear [77]. In vitro experiments by domestic scholars have shown icariin combined with exercise coupling stimulation may inhibit bone resorption by regulating NF-κB signaling and influence the upregulation of OB proliferation by the classical Wnt/β-catenin pathway.…”
Section: Antimenopausal Osteoporosis Effects Of Exercise Combined With Natural Extractsmentioning
confidence: 99%
“…It was reported that β-catenin, Akt, ERα, and Runx2 expression were significantly increased in OB in the treadmill-bound Epimedii intervention group, compared with exercise alone. Combination treatment significantly prevented OVX-induced bone loss and increased OB differentiation and mineralization ability, some of which may be regulated by the ERα/Akt/β-catenin pathway, but whether combination intervention affected OC differentiation remains unclear [77]. In vitro experiments by domestic scholars have shown icariin combined with exercise coupling stimulation may inhibit bone resorption by regulating NF-κB signaling and influence the upregulation of OB proliferation by the classical Wnt/β-catenin pathway.…”
Section: Antimenopausal Osteoporosis Effects Of Exercise Combined With Natural Extractsmentioning
confidence: 99%
“…Exercise-induced skeletal adaptation to ICA therapy was enhanced in part by the ER/AKT/β-catenin pathway. 66 ICA promotes bone formation in osteoblasts in rats by activating the cAMP pathway, which is localized to osteoblast primary cilia, as demonstrated by siRNA suppression of a protein involved in cilium assembly. 54 This research strengthened the link between cAMP-mediated signaling and osteogenesis and provided fresh insights into the mechanism and function of ICA.…”
Section: Mechanisms Of Icariin In Anti-osteoporosismentioning
confidence: 96%
“…89 Exercise enhanced this process via upregulating the expression of ERα and then strengthening the Akt/β-catenin pathway. 66 Specific MAPK inhibitors, including the JNK inhibitor SP600125 and the ERK inhibitor U0126, reduced the effects of ICA on osteoblast differentiation. ICI182780, an ER antagonist, decreased ICA-mediated effects and prevented ERK and JNK phosphorylation, indicating that ICA's activation of the ER signaling pathway also activates the ERK and JNK pathways.…”
Section: Icariin Regulates Migration Proliferation and Differentiatio...mentioning
confidence: 99%